2021
DOI: 10.3390/polym13203486
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Novel Compatibility Strategies for Improving the Performance of Recycled Low-Density Polyethylene Based Biocomposites

Abstract: The interfacial compatibility of the natural filler and synthetic polymer is the key performance characteristic of biocomposites. The fillers are chemically modified, or coupling agents and compatibilisers are used to ensure optimal filler-polymer compatibility. Hence, we have investigated the effect of compatibilisation strategies of olive pits (OP) flour content (10, 20, 30, and 40%wt.) filled with recycled low-density polyethylene (rLDPE) on the chemical, physical, mechanical, and thermal behaviour of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Similarly, the present authors previously reported the in situ grafting of immiscible HDPE‐PVC blends with MAH initiated by dicumyl peroxide (DCP) using a twin screw extruder 14 . Recently, several researchers have reported the preparation of bio‐composites and have investigated the effects of treated fiber and matrix maleation 15–17 . Other studies have reported that MAH forms bridges between both the hydroxyl groups of the fibers and the polymer matrix 18,19 …”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, the present authors previously reported the in situ grafting of immiscible HDPE‐PVC blends with MAH initiated by dicumyl peroxide (DCP) using a twin screw extruder 14 . Recently, several researchers have reported the preparation of bio‐composites and have investigated the effects of treated fiber and matrix maleation 15–17 . Other studies have reported that MAH forms bridges between both the hydroxyl groups of the fibers and the polymer matrix 18,19 …”
Section: Introductionmentioning
confidence: 54%
“…14 Recently, several researchers have reported the preparation of bio-composites and have investigated the effects of treated fiber and matrix maleation. [15][16][17] Other studies have reported that MAH forms bridges between both the hydroxyl groups of the fibers and the polymer matrix. 18,19 The mechanical upcycling of the HDPE-PVC blend is a desirable process for improving the thermo-physical performance and reducing the environmental impact of plastic waste.…”
Section: Introductionmentioning
confidence: 99%
“…CNPs [P] show lower compatibility with the PP matrix than CNPs [M]. The lower compatibility is evidenced by the presence of exposed CNPs after cryogenic shearing and by the presence of microvoids/cavities at the interface CNPs‐PP 48–51 . In Figure 3, a more significant number of exposed CNPs [P] can be observed (indicated with red arrows), as well as a more considerable number of microvoids are observed at the interface between CNPs [P] and PP matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The lower compatibility is evidenced by the presence of exposed CNPs after cryogenic shearing and by the presence of microvoids/cavities at the interface CNPs-PP. [48][49][50][51] In Figure 3, a more significant number of exposed CNPs [P] can be observed (indicated with red arrows), as well as a more considerable number of microvoids are observed at the interface between CNPs [P] and PP matrix. Figure 4 shows the CNFs [M] less exposed and covered by thin layers of the PP, as well as the absence of microvoids in the interface of the exposure of the CNFs [M].…”
Section: Compatibility Of Cnps With Pp Matrixmentioning
confidence: 99%
“…[19][20][21] Surface modification of polymers can be utilized to improve biological resistance, compatibility or degradability, impact response, thermal stability, multiphase physical response, flexibility, stiffness, and other properties. [22][23][24] According to the literature, the most common PVA modification processes involving hydroxyl groups are esterification, etherification, and acetalization. [14,25] Several other schemes for the modification of synthetic and natural polymers, each targeting a specific application, have been reported in previous literature.…”
Section: Introductionmentioning
confidence: 99%